Screening of Secondary metabolites of Endophytic fungi Alternaria alternata Isolated from Microstachys chamaelea (L) Muell.Arg. - B.C. Kavya; Kavya C S; Kalpashree M.M; Krishna K (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Endophytes are the treasure biopotential sources for the active biocompounds which can be used as pharmaceuticals and agrochemicals. In the current study, endophytic fungi Alternaria alternata isolated from Microstachys chamaelea was investigated. Ethyl acetate extract of the endophytic fungal metabolite was screened by Gas Chromatography - Mass Spectrometry technique. The identified biocompounds are Phthalic acid-cyclobutyl tridecyl ester, Phthalic acid-cyclobutyl isobutyl ester, Phthalic acid- 4-bromophenyl octyl ester, Phthalic acid- 4-cyanophenyl nonyl ester, Phthalic acid- 6-ethyl-3-octyl butyl ester, Phthalic acid- cyclobutyl tetradecyl ester, Phthalic acid- 4-nitrophenyl octyl ester, Phthalic acid- cyclobutyl hexyl ester, Phthalic acid-cyclobutyl heptyl ester and Phthalic acid-heptyl pentyl ester. These findings suggest that only Pthalic acid derivative secondary metabolites were found in the isolated Endophytic fungi Alternaria alternata from Microstachys chamaelea. These bioactive compounds could be used in the development of antimicrobial agents.